STRATEGI SHADOW TEACHER DALAM MENGATASI KESULITAN BERKOMUNIKASI ANAK BERKEBUTUHAN KHUSUS (ABK) TUNA RUNGU - Amirulloh Sismawijaya; Anita Puji Astutik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Inclusive education is an educational framework that seeks to ensure fair access to education for all individuals, including children with special needs, one of which is deaf children. This research was motivated by the difficulties of deaf children at SLBN Juwetkenongo in communicating with other people. The causes include physical barriers (unable to grasp information clearly) and language barriers (children's ignorance and lack of understanding of sign language vocabulary). This research aims to determine shadow teachers' strategies in overcoming communication difficulties for deaf children at SLBN Juwetkenongo. This research is classified as qualitative research with a qualitative descriptive approach because it relies mostly on data obtained from observations and interviews with individuals. The research was carried out on May 17 2024 at SLBN Juwetkenongo involving the main informants as grade 4 shadow teachers. The results of this research found that the strategies possessed by shadow teachers to overcome the communication difficulties of deaf children include the following: 1) Letter recognition method, 2) Introduction method through pictures, 3) Outdoor learning methods.